Analyzing Consumer Behavior in Stockpiling Food Commodities During Crisis: a Case Study of the 2023 Gaza War - ALSHAFEI, TAGHREED (İstanbul Kültür Üniversitesi, 2025)
This study explores the behavior of stockpiling for food commodities during times of crises, with a focus on wheat flour as the subject of study during the ongoing Gaza War in 2023. Flour is considered one of the most crucial food items that residents of Gaza sought to stockpile, as it plays a vital role in ensuring food security and protecting against hunger. The study analyzes the economic, situational, social, and psychological factors influencing individuals' decisions to stockpile this commodity. A survey was used to collect data from citizens in different areas of the Gaza Strip, and the data was analyzed using the SPSS software. The results revealed a strong correlation between the studied factors and the decision to stockpile, indicating the importance of understanding these factors to predict consumer behavior during crises. Based on these findings, several recommendations were provided to improve stock management strategies and deal with future crises.
Keywords: Consumer Behavior; Stockpiling; Food Commodities; Food Security; Crisis; Gaza War 2023; Crisis Management; Economic Factors; Situational Factors; Social Factors; Psychological Factors